Classical Reconstruction in Visual Narration: An Aesthetic Analysis of the Reception of Sun Wukong's Image - Li, Ruohan (International Journal of Social Sciences and Public Administration, 2024)
Sun Wukong, as the iconic hero image in Chinese traditional culture, has various forms of expression in visual narration, which is deeply loved by audiences of all ages. With the progress of technology and aesthetic changes, the visual image of Sun Wukong has undergone a transformation from sacred to secular, and then to personalized. This paper aims to explore the remodeling process of Sun Wukong in different visual media from the perspective of reception aesthetics, analyze how audiences accept and interpret these images, and how these changes reflect the evolution of social culture.